2013
DOI: 10.1212/wnl.0b013e3182a6cc13
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune disease preceding amyotrophic lateral sclerosis

Abstract: Objective: To study whether the risk of amyotrophic lateral sclerosis (ALS) is increased in people with prior autoimmune disease.Methods: An all-England hospital record-linkage dataset spanning 1999-2011 was used.Cohorts were constructed of people with each of a range of autoimmune diseases; the incidence of ALS in each disease cohort was compared with the incidence of ALS in a cohort of individuals without prior admission for the autoimmune disease.Results: There were significantly more cases than expected of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
136
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(155 citation statements)
references
References 28 publications
15
136
3
1
Order By: Relevance
“…jci.org Volume 127 Number 9 September 2017 asthma, celiac disease, juvenile-onset diabetes, multiple sclerosis (MS), myasthenia gravis, systemic lupus erythematosus, and ulcerative colitis, supporting that autoimmune diseases and ALS might share common genetic or environmental risk factors (125). Other recent studies found an increased prevalence of autoimmune diseases in FTD with TDP-43 pathology (126), and specifically in C9orf72 patients with ALS/FTD (127).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 97%
“…jci.org Volume 127 Number 9 September 2017 asthma, celiac disease, juvenile-onset diabetes, multiple sclerosis (MS), myasthenia gravis, systemic lupus erythematosus, and ulcerative colitis, supporting that autoimmune diseases and ALS might share common genetic or environmental risk factors (125). Other recent studies found an increased prevalence of autoimmune diseases in FTD with TDP-43 pathology (126), and specifically in C9orf72 patients with ALS/FTD (127).…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 97%
“…Some other studies have related motor neuron disease with autoimmune neuromuscular disorders. Around 30% of ALS patients present decrement on repetitive nerve stimulation [181], and the risk of ALS is increased in people with concomitant myasthenia gravis [182]. This combination of ALS and myasthenia gravis has been reported to occur non-stochastically [183] and, although the reasons for the coincidence are unknown, it may involve a link between the immune system and ALS [156].…”
Section: Is Als a Neuroinflammatory Disease?mentioning
confidence: 99%
“…According to the results from the study made by Turner et al, it seems that more cases than expected of ALS are associated with a prior diagnosis of asthma, celiac disease, younger-onset diabetes (younger than 30 years), multiple sclerosis, myasthenia gravis, myxedema, polymyositis, Sjögren syndrome, systemic lupus erythematosus and ulcerative colitis were confirmed, concluding that ALS raise the possibility of shared genetic or environmental risk factors [55]. These findings encouraged us to look into more groups of famous peoples to continue looking for the co-existence of ALS and other diseases.…”
Section: What About Other Famous Sportsmen?mentioning
confidence: 97%